PENERAPAN METODE DEPRESIASI AKTIVA TETAP PADA PT RAMARINDA PADANG ULAK TANDING - Berlian Afriansyah (Politeknik Raflesia Press, 2020)
The purpose of this study was to find out the application of the fixed asset depreciation method at PT.Ramarinda Padang Ulak Tanding. The depreciation method used in this study is the Straight Line and Decreasing Balance Method. The fixed assets calculated for depreciation are machines that are included in group assets with a depreciation rate of 5% for the Straight Line Method and 10% for the declining balance method with a 20-year economic life, namely the Exsa and Loader type machine. The results of this study can be concluded that the Straight Line depreciation method produces a yearly depreciation expense with a fixed amount which is Rp. 40.000.000 to a Loader machine and Rp. 37.500.000 to Exsa Machine while the Decreasing Balance method produces a smaller depreciation load each year which is Rp 11.887.947,524 to Loader machine and Rp 10.167.435,460 to Exsa Machine.